Conservation Value of Gunungan Wayang Kulit Purwa for Science Learning Materials - Fahrudin, D.; Saputro, S.; Sarwanto, S.; Sauli, S. S.; QiaoLu, Q. (Jurnal Pendidikan IPA Indonesia, 2023)
This study aims to explore the concepts of ecology and biodiversity, the value of environmental preservation in gunungan wayang kulit purwa, and its correlation to science learning or environmental education in a science subject at the junior high school level to increase environmental awareness. This research employed a qualitative descriptive approach. This research included ethnographic research associated with symbolic interpretation in anthropology. The informants of this study were a puppeteer (dalang), a javanology expert, a gunungan wayang kulit purwa creator, and a biodiversity expert chosen by purposive sampling. Data were collected through semi-structured interviews, literature reviews, and content analysis. Data triangulation was applied to ensure the data validity. The data were analyzed using a spiral analysis model, including managing, reading, marking, describing, classifying, interpreting, and visualizing data continuously. The study results show that the gunungan wayang kulit purwa contains the conservation value and concept of ecology and biodiversity. This concept has a correlation with the material on ecology and biodiversity in the independent curriculum in a science subject at schools. The ecological concept includes biotic and abiotic components, symbiosis, pollinators and predators, food chains, food webs, competition, and the value of environmental preservation. The findings in the form of a link between ecological concepts and biodiversity in the gunungan wayang kulit purwa have implications for the potential use of gunungan wayang kulit purwa as a learning resource for science education in schools or environmental education to increase environmental awareness of the young generation.